A classical archaeologist's life : the story so far : an autobiography - Boardman, John, 1927- (Archaeopress archaeological lives., 2020)
Sir John Boardman is one of the foremost experts on ancient Greek art. His autobiography offers a mixture of scholarly reminiscence, reflection on family life, travelogue and critique of classical scholarship worldwide. Illustrated with pictures of travels, friends and home life, it reflects on his experiences of more than 90 years.